Estratégias discursivas para a narração de um crime: uma análise semiótica da série O Caso Evandro - Luíza Martins dos Santos (2024)
The present work seeks to understand how the true crime documentary series, O Caso Evandro, is discursively organized in terms of narrative strategies. The series, launched in 2020 and organized into nine episodes, tells the story of the boy Evandro who disappeared in Paraná in the 90s and the consequences of this case. Our general objective, in this research, is to try to understand how these discursive and narrative mobilizations represented the crime and the accused involved in the series' plot. For this, we use French Semiotic theory as a reference, supported by the works of several authors such as Barros (2002; 2005), Fiorin (2001; 2012), Greimas (2014), Fontanille and Tsala-Effa (2019), Matte (2005), among others, to answer our research question about the strategies that constructed the effects and opinions of meaning in the work. Based on a precise methodological approach, we listed as a final corpus the moments of the series that would be of interest to us, prioritizing, in this sense, five sets of scenes that harbored doubts regarding the actual effects on the plot. The analysis is organized into three minimal narratives and examines the different actantial positions assumed by the discursive actors in the series, investigates narrative manipulations and transformations in the narrative paths, studies the themes and figures located in the plot and examines the projections of person and time in the utterance . In view of the analysis of our research object, we came to the conclusion that the series discursively guides its narrative strategies to exonerate the accused, updating their image to those enunciated in the production. Our results allow us to say that, although there is a diversity between the actantial positions that the actors assume throughout the plot, the plot constructs, from the beginning, an attempt to redeem the accused through the narrative and discursive strategies present in the work. Furthermore, we also consider that the opinions expressed by the narrator are used as sanctions, positive or negative, for the actants, guiding the apprehension of the image of the accused and others involved by the narratees/enunciatees of the work. We conclude our research by addressing some possible paths for analyzing content from the documentary genre and the universe of true crimes, as well as encouraging the use of French Semiotics in this type of object of study, considering the contributions of its applicability.